An assessment of bicycle frame behaviour under various load conditions using numerical simulations - Covill, D.; Allard, P.; Drouet, J.-M.; Emerson, N. (Procedia Engineering, 2016)
This paper outlines the use of a finite element model to simulate the behaviour for a standard steel bicycle frames under a range of measured load cases. These load cases include those measured both in the laboratory setting and also in the field, and include loads transmitted at key areas such as the dropouts and hub, the bottom bracket and drive, the headset and handlebars, and the seat post and saddle. The load cases analysed include static representations of dynamic bump situations which occur sporadically and also those which occur constantly or regularly such as those generated at the drive and handlebars during climbing or cruising. The resulting stresses within the bicycle are analysed in the context of frame performance relating to static and fatigue strengths and are also compared to similar load cases presented in the literature. Further research is required to understand the influence of tube profiles on frame strength, and to analyse the modes of failure for various bicycle designs and materials used under typical and extreme usage in order to understand the implications of design on safety.